2009
DOI: 10.1017/s1368980009990711
|View full text |Cite
|
Sign up to set email alerts
|

Are snacking patterns associated with risk of overweight among Kahnawake schoolchildren?

Abstract: Objective: To understand more specifically how the quality, quantity and frequency of snack food consumption differs in different BMI categories. Design: Four hundred and forty-nine school-aged children (grade 4-6) from a Kanien'kehaka (Mohawk) community provided a 24 h recall and their height and weight in 1994, 1998 and 2002, in three independent cross-sectional samples. Food consumed between two consecutive meals was defined as a snacking occasion. ANOVA and x 2 tests were used to compare food choices betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
3
33
0
2
Order By: Relevance
“…In fact, our data showed that for all years examined, either grain-based desserts or salty snacks were the number one source of sodium intake from snacking (Supplementary Table S3). Our findings are also supported by research from other countries which has shown, not only that the foods consumed as snacks are generally from less healthy food groups [23], but that disparities exist between various race-ethnic and education groups [24,25,26,27]. …”
Section: Discussionsupporting
confidence: 88%
“…In fact, our data showed that for all years examined, either grain-based desserts or salty snacks were the number one source of sodium intake from snacking (Supplementary Table S3). Our findings are also supported by research from other countries which has shown, not only that the foods consumed as snacks are generally from less healthy food groups [23], but that disparities exist between various race-ethnic and education groups [24,25,26,27]. …”
Section: Discussionsupporting
confidence: 88%
“…[14][15][16][17][18][24][25][26][27][28] The majority of studies that investigated whether there is a relationship between snacking behavior and weight status either found no association 19,33,[41][42][43]45,46,48,49,[52][53][54]59 or found evidence indicating that young people who more often consumed food or beverages between meals were less likely to be obese. 21,30,32,34,37,38,55,57 However, a smaller number of studies found evidence indicating the frequency of snacking, percentage of energy consumed at snacks, or greater consumption of energy-dense snack foods was associated with increased risk for obesity among some groups, 31,35,36,44,47,50,51,56,58 and two studies found that more frequent snacking in front of the television was associated with higher BMI. 39,40 Additional research is needed to address various methodological limitations and knowledge gaps so that the relationship between snacking behaviors and weight status may be elucidated and the design of nutrition interventions better informed to promote the consumption of healthfu...…”
Section: Discussionmentioning
confidence: 99%
“…We noted that the definition of snacking varied across studies, which might contribute to the incongruence of study findings. Some studies defined snacking in terms of frequency of consumption (31)(32)(33)(34)(35) , while others treated the variable as the sum of total daily servings of snack food items (8,9) . Additionally, because the quality of Table 3 Mean annual change in indicators of adiposity according to soda intake*: children (n 961) aged 5-12 years, Bogotá , Colombia *Estimated mean values with their standard errors and unadjusted differences are from mixed-effects linear regression models with the adiposity measure as the outcome and predictors that included indicator variables for soda intake categories, age in decimal years, and soda intake categories 3 age interaction terms.…”
Section: Discussionmentioning
confidence: 99%